ANALISIS KECURANGAN DALAM PELAPORAN KEUANGAN:BAGIAN DARI BUKTI RASIO KEUANGAN - Ade Onny Siagian; Adler Haymans Manurung; Tri Widyastuti; Sugeng Suroso (Jurnal Bisnis Terapan, 2024)
The case study related to the abuses of financial reports is damaging the trust of the public and stakeholders. This research was designed to identify and evaluate the importance of financial ratios in identifying potential fraudulent financial statements of non-financial companies on the Indonesia Stock Exchange. These companies were selected based on the Beneish M-Score as the first sign of fraud. The results of the analysis show that the debt to equity ratio, receivables to income, and current ratio indicate the possibility of fraud. Analyzing the period 2019 to 2023, we find that the current ratio can detect fraud a year earlier. These results suggest that metrics such as debt to equity, receivables to revenue, and current ratio can help detect fraud, potentially benefiting shareholders, regulators, and creditors. The results of this study was still in line those studies which have been conducted before in different parts of Indonesia and at the time or period of time.